Refractive index measurements in a reentrant discotic nematic–biaxial nematic phase transition. (3rd August 2018) - Braga, W.S.; Luders, D.D.; Santos, O.R.; Sampaio, A.R.; Kimura, N.M.; Simões, M.; Palangana, A.J.
ABSTRACT: The optical characterization of uniaxial (reentrant discotic – N Dr and discotic – N D ) and biaxial nematic (N B ) phases requires the measurements of two and three refractive indices, respectively. These optical parameters were determined near the reentrant isotropic ( I r ) − N Dr − N B − N D -isotropic ( I ) phase transitions in a lyotropic mixture of potassium laurate, decanol and D 2 O . Biaxial positive (N B + ) nematic phase is optically characterized between two uniaxial discotic nematic phases from refractive index data and confirmed via conoscopic images. The micellar configuration of uniaxial and biaxial nematic phases is discussed as a consequence of our experimental data.